Interventions for family involvement enhance end-of-life care for hospitalized patients: an integrative review - Yujin Kim; Dong-Hee Kim (BMC Nursing)
Abstract Background Integrating family members into the care of hospitalized end-of-life patients enhances patient–family-centered care and significantly influences the experiences of patients and their families. This study used the integrative review methodology to assess the scope and effectiveness of interventions designed to facilitate family involvement in end-of-life care. It identified gaps and consolidated existing knowledge to improve nursing practices. Methods This integrative review encompasses both experimental and non-experimental studies. The process included problem identification, literature search, data evaluation, analysis, and integration. The literature search targeted studies describing interventions for family involvement in EOLC using databases such as PubMed, CINAHL, Embase, and Web of Science. Data evaluation was conducted by assessing the quality of the studies using the Mixed Methods Appraisal Tool. Data analysis and integration were conducted by synthesizing the results of the selected studies and identifying the elements of family involvement using the 'Components of Family Involvement' framework. Results Of the 8,378 identified studies, 26 were eligible for inclusion. Interventions involving the families of patients with terminal illness varied, including programs to enhance communication among patients, families, and healthcare providers; family meetings; decision-making support; and digital visits and rounds. The findings show that these interventions improve patients’ psychological and physical comfort, family satisfaction, and communication. However, some families reported increased distress. The most frequently addressed elements of family involvement were communication and receiving information, followed by decision-making and meeting care needs. Family presence and contribution to care were the least addressed elements in the interventions. Conclusions This integrative review highlights the effectiveness of interventions to increase family involvement in end-of-life care, demonstrating positive impacts on patient comfort, family satisfaction, and communication. Despite progress in incorporating families into communication and decision-making, further efforts are needed to ensure their presence and direct care involvement. Future research should focus on improving these interventions to enhance scalability and support comprehensive family involvement, including digital tools for participation.